Epidemiological profile of the pediatric population with clinical and subclinical hypothyroidism in the Intermunicipal Health Consortium of West Paraná - CISOP (Research, Society and Development, 2023)
The thyroid gland is of paramount importance for human development, due to the important action of its hormones for the human body. In view of this, thyroid alterations affect human beings too much, especially children and adolescents, since it is a period in which the organism is in constant growth and development, therefore, deficiencies in the production and/or action of thyroid hormones, lead to several problems, especially in this period. Therefore, this research aimed to evaluate the epidemiological profile of pediatric patients between 0 and 12 years old, diagnosed with clinical and subclinical hypothyroidism undergoing treatment at a pediatric endocrinology service in western Paraná. Eighty-five children were evaluated, with females being the most affected in the sample. Acquired clinical hypothyroidism was the most frequent diagnosis, largely due to Hashimoto's thyroiditis. Furthermore, all cases were classified as primary hypothyroidism. Changes in TSH results in routine exams were the main complaint that led to referral to the specialized service. Also, it could be inferred that the physical examination at the time of diagnosis was quite nonspecific, and mostly without characteristic changes of the disease. Down syndrome was found to be the pre-existing condition most associated with the diagnosis of hypothyroidism. Finally, it was found that most of the individuals studied were using levothyroxine as a form of treatment for the diagnosed condition.